PENGARUH LATIHAN frog jump TERHADAP POWER OTOT KAKI DAN PENERAPANNYA DALAM KEMAMPUAN SHOOTING SEPAK BOLA DI SSB BIAWAK TAPUNG KABUPATEN KAMPAR - Rahmat Hidayat; Agus Prima; Alimandan , (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2025)
ABSTRACTThis study aimed to determine the ef ect of frog jump training on legmuscle power and its application to soccer shooting ability among athletes of SSBBiawak Tapung, Kampar Regency. This research employed a quantitativeapproach using a one group pretest–posttest design. The sample consisted of 15soccer athletes selected through total sampling. The frog jump training programwas conducted over 16 training sessions with a frequency of three sessions perweek, in addition to two sessions for administering the pretest and posttest. The instrument used to measure leg muscle power was the standing longjump test, while soccer shooting ability was measured using a shooting skill test. The collected data were analyzed using a paired sample t-test with a significancelevel of 0.05. The results of the data analysis indicated that frog jump training hada significant ef ect on improving leg muscle power, with a significance value of0.000 0.05. These findings demonstrate that frog jump training is ef ective inenhancing the explosive power of the lower limb muscles in soccer athletes. However, the analysis of the shooting ability variable showed asignificance value of 1.000 0.05, indicating that frog jump training did not havea significant ef ect on soccer shooting ability. Therefore, it can be concluded thatfrog jump training is ef ective in improving leg muscle power but has not yetshown a significant ef ect on the application of soccer shooting ability amongathletes of SSB Biawak Tapung, Kampar Regency. Keywords: frog jump, leg muscle power, shooting ability, soccer.